Development of Learning Materials for English Engineering Course: ESP (English for Specific Purpose) with a Functional Contextualism Approach for Mechanical Engineering Students of South Aceh Polytechnic - Jannah, Dina Miftahul (LPPM Politeknik Aceh Selatan, 2022)
The students of mechanical engineering at vocational college must be able to communicate in English, both written and spoken, using the specific term related to their department, and need to learn vocabulary with the integration of technology to confront the world of work. The study aimed to develop the English learning materials for specific purposes specifically for mechanical engineering students through functional contextualism approach. The study employed the qualitative descriptive method. The subjects of this study were English lecturers and mechanical engineering students of the South Aceh Polytechnic in grades II. The data were collected by interviews, observations, and questionnaires. Data analysis with data classification, transcription, verification, and conclusions. The results of the study showed that development of English language teaching materials for mechanical engineering study programs based on the ESP and functional contextualism approach includes in the form of textual development packages, namely (1) textbooks (2) lecturer guides and (3) student guides. The purpose of the development is that learners can improve the quality of their learning outcomes in English Engineering and use them in the workplace (market place). In other words, the material also develop based on the context of their surroundings, like integrated approaches, functional contextualism blends sociocultural and historical context, but with the pragmatic and scientific aims of behaviour analysis. In addition to taught and constructed learning, functional contextualists suggest functional change in meaning is the process of recontextualization.